Prevention of doxorubicin sorptive losses in drug delivery studies using polyethylene glycol. Issue 33 (11th March 2015) - Curry, Dennis; Scheller, Hope; Lu, Mingsheng; Mkandawire, Martin; Servos, Mark R.; Cui, Shufen; Zhang, Xu; Oakes, Ken D.
Abstract : Polyethylene glycol enhances the accuracy of drug delivery system evaluations by preventing sorptive losses of hydrophobic drugs to plastic reaction vessels. Abstract : The nonspecific sorption of hydrophobic pharmaceuticals on reaction vessel surfaces raises serious analytical challenges for their accurate quantification. Systematic error due to sorptive loss of analytes may result in significant overestimation of drug loading on nanomaterial-based Drug Delivery Systems (DDS), leading to inaccurate determinations of dosage and DDS efficiency. We evaluated sorptive losses of doxorubicin (DOX), an effective chemotherapeutic, in polystyrene based 96-well plates, and proposed a simple but effective method to prevent the nonspecific sorption of DOX using trace concentrations of polyethylene glycol (PEG). Relative to widely used proteinaceous and surfactant surface blocking agents, PEG is effective, easy to use, and does not interfere with drug loading to the DDS.